STRATEGIES IN THE TRANSLATION OF AN ENGLISH NOVEL THEY DO IT WITH MIRRORS: SYNTACTIC AND SEMANTIC APPROACHES - Veronica Cinthya Tamara; Evert H. Hilman; Ahmad Mustolih (PROJECT (Professional Journal of English Education), 2022)
This research is aimed to find out and analyze the theories used to translate an English novel ‘They Do It with Mirrors’ into Indonesian. The method used here is descriptive qualitative. The procedure of the research were reading both versions of the novel (English and Indonesian), marking the problems, collecting the problems, and analyzing the data focusing on Chesterman’s translation strategies with other supportive theories. This research shows that the most commonly used strategies are cohesion change, unit shift, and transposition. Cohesion change and unit shift can occur from phrase to words or vice versa, but transposition only occurs from word to word. Keywords:  Translation Strategy, Unit Shift, Cohesion Change, Transposition